2018
DOI: 10.1155/2018/5407482
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Modulates DNA Methyltransferase Functions in a Cellular Model of Diabetic Retinopathy

Abstract: Hyperglycaemia-induced oxidative stress appears to be involved in the aetiology of diabetic retinopathy (DR), a major public health issue, via altering DNA methylation process. We investigated the effect of hyperglycaemia on retinal DNA methyltransferase (DNMT) expression in diabetic mice, using Gene Expression Omnibus datasets. We also evaluated the effect of curcumin both on high glucose-induced reactive oxygen species (ROS) production and altered DNMT functions, in a cellular model of DR. We observed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 69 publications
1
51
0
1
Order By: Relevance
“…This study had some limitations. Although hypomethylation of transposable repetitive elements, including LINE-1 sequences, has been associated with chromosomal instability and aberrant genome function ( Schulz, 2006 ; Slotkin and Martienssen, 2007 ) and with different chronic degenerative diseases ( Baccarelli et al, 2010 ; Woo and Kim, 2012 ; Barchitta et al, 2014b ; Maugeri et al, 2018b ), mechanisms of DNA hypomethylation are not fully understood. Therefore, the cross-sectional design of our analysis arises the need of further prospective studies and of functional test to explore the causes and the consequences of these modifications and to better understood the biological significance of LINE-1 methylation alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study had some limitations. Although hypomethylation of transposable repetitive elements, including LINE-1 sequences, has been associated with chromosomal instability and aberrant genome function ( Schulz, 2006 ; Slotkin and Martienssen, 2007 ) and with different chronic degenerative diseases ( Baccarelli et al, 2010 ; Woo and Kim, 2012 ; Barchitta et al, 2014b ; Maugeri et al, 2018b ), mechanisms of DNA hypomethylation are not fully understood. Therefore, the cross-sectional design of our analysis arises the need of further prospective studies and of functional test to explore the causes and the consequences of these modifications and to better understood the biological significance of LINE-1 methylation alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation level of transposable sequences, including both long interspersed nucleotide elements 1 (LINE-1) and Alu sequences, has been used as a surrogate marker of global genomic DNA methylation ( Yang et al, 2004 ). Although LINE-1 methylation is not an universally accepted marker of global methylation, aberrant methylation of these sequences was shown to be associated with cancer ( Woo and Kim, 2012 ; Barchitta et al, 2014b ), CVD ( Baccarelli et al, 2010 ), and degenerative diseases ( Maugeri et al, 2018a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Quinocetone causes genotoxicity and oxidative stress in human hepatocyte L02 cells, and curcumin pretreatment markedly inhibits excessive ROS generation, with the suppression of the decrease in the activity of antioxidant enzymes, like superoxide dismutase (SOD), and levels of antioxidant constituents, such as glutathione (GSH) [ 29 ]. In addition, in diabetic mice, curcumin treatment inhibits ROS production and hyperglycemia-induced oxidative stress by restoring the functions of DNA methyltransferase (DNMT) [ 30 ].…”
Section: Bioactivity Of Curcuminmentioning
confidence: 99%
“…Another member of the antioxidant network, GSTP1 , was also found to be demethylated and activated upon exposure of breast cancer cells to curcumin (Kumar, Sharma, & Rathi, ). Furthermore, Maugeri et al () reported up‐regulation of DNMT1 expression and activity along with oxidative stress induced by chronic high glucose levels in a cellular model of diabetic retinopathy (Maugeri et al, ). Interestingly, curcumin restored normal levels of DNMT1 and inhibited the overproduction of ROS (Maugeri et al, ).…”
Section: Interrelationship Between Antioxidant Properties and Dna Metmentioning
confidence: 99%
“…Furthermore, Maugeri et al () reported up‐regulation of DNMT1 expression and activity along with oxidative stress induced by chronic high glucose levels in a cellular model of diabetic retinopathy (Maugeri et al, ). Interestingly, curcumin restored normal levels of DNMT1 and inhibited the overproduction of ROS (Maugeri et al, ).…”
Section: Interrelationship Between Antioxidant Properties and Dna Metmentioning
confidence: 99%